Explorations into highland New Guinea, 1930-1935 - Leahy, Michael J., 1901-1979 (Book collections on Project MUSE., 1991)
In the 1920's and 1930's there were adventures to be lived and fortunes to be made by strong young men in the outback of Australia and the gold fields of New Guinea. This is the diary of five years spent in hot pursuit-not of honor and glory, but of excitement and riches-by one such adventurer, Michael ""Mick"" Leahy, his brothers Jim and Pat, and friends Mick Dwyer and Jim Taylor. Leahy and his associates explored the unknown interior of New Guinea, seeking gold and making contact for the first time with the aborigines of the interior mountains and valleys. White man